Cell cycle control by the ubiquitin system in mammals - Pagano, Michele (Henry Stewart Talks, 2009)
Ubiquitin-proteasome system, What regulates the cell division cycle?, Cyclin dependent kinases, Advantages of regulated proteolysis, The hierarchy of the ubiquitin pathway, E2s and E3s ensure substrate specificity, Regulation of the cell cycle by proteolysis, Two major ubiquitin ligases control cell cycle progression, SCF ubiquitin ligases, Mechanism of catalysis by the SCF, F-box proteins, Skp2, betaTrcp1 and betaTrcp2, DNA replication stress, Fbxw7, Anaphase promoting complex or cyclosome, Cell cycle, ubiquitin system and cancer